Physical Activity and Physiological Profiles of Elite International Female Field Hockey Players Across the Quarters of Competitive Match Play. Issue 9 (September 2019) - McGuinness, Aideen; Malone, Shane; Hughes, Brian; Collins, Kieran; Passmore, David
Abstract : Abstract: McGuinness, A, Malone, S, Hughes, B, and Collins, K. Physical activity and physiological profiles of elite international female field hockey players across the quarters of competitive match play. J Strength Cond Res 33(9): 2513–2522, 2019—The aim of the current investigation was to quantify the physical and physiological demands of elite international female field hockey across the quarters of match-play. Twenty-seven elite international female field hockey outfield players (23 ± 3 years; 162.6 ± 13.0 cm; 66.0 ± 6.0 kg) participated in the current observational study during the 2016–2017 season. Participants were monitored using global positioning system technology and HR monitors. Players were categorized based on 3 different playing positions. Activity was categorized into total distance (in meters), relative total distance (m·min −1 ), low-, moderate-, and high-intensity distance (m), maximum velocity (km·h −1 ), and percentage maximal velocity (%). Physiological demands were quantified through players peak heart rate (HRPeak ), which was classified based on the player's individual HRmax determined using a Yo-Yo intermittent recovery level 1 test. Players spent on average 38 ± 8 minutes in match play. The total distance covered was 4, 847 ± 583 m (127.6 ± 15.6 m·min −1 ). Defenders covered a greater total distance across all 3 positions ( p = ⩽ 0.05). The midfielders covered a greater moderate-intensity distance ( p ⩽ 0.001), whereas the forwards covered more high-intensity distance ( p ⩽ 0.001). The HRpeak of the players was 198 ± 4 b·min −1 with a mean exercise intensity of 95 ± 1% HRmax . The time spent >70% HRmax decreased significantly across the quarters ( p = 0.01, η 2 = 0.03). Defenders were found to spend more time >85% HRmax when compared with other positions ( p ⩽ 0.001, η 2 = 0.28). The current study provides normative data that coaches should consider when developing training drills to better optimize the positional physical and physiological activity profiles that best replicate match play.